PENGARUH GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA PESERTA DIDIK DI SEKOLAH DASAR - Feby Inggriyani; Astri Wulan Samosir (STKIP Subang, 2022)
ABSTRACT This study aims to find out (1) an overview of the implementation of the School Literacy Movement (GLS), (2) how much influence the implementation of the GLS has on students' reading interest, (3) the obstacles in implementing the GLS and (4) the efforts made to overcome obstacles in GLS implementation. The method used is a survey method with a quantitative approach by distributing questionnaires and interviews for data collection. The results of the study showed: (1) the implementation of GLS at SDN 006 Buahbatu, SDN 184 Buahbatu, SDN 246 Margacinta and SDN 095 Kebonjati had been carried out in accordance with the habit of reading 15 minutes before the KBM started, there was a reading corner in each class equipped with various reading books, ( 2) there is an influence between GLS on reading interest of class IV students of 29.7%, (3) there are several obstacles in the implementation of GLS including students feeling bored quickly while reading, lack of funds to support facilities for implementing GLS, lack of variety of book variations provided, and finally the lack of interest of students to visit the library, (4) efforts that can be made to overcome existing obstacles include doing ice breaking so students don't feel bored, making proposals regarding funds to the government to support facilities in implementing GLS by preparing various types of reading materials, and managing the library with s interesting as possible in order to attract the interest of students. Keywords: School Literacy Movement, Reading Interest, Elementary School ABSTRAK Penelitian ini bertujuan untuk mengetahui (1) gambaran umum pelaksanaan Gerakan Literasi Sekolah (GLS), (2) seberapa besar pengaruh pelaksanaan GLS terhadap minat baca peserta didik, (3) hambatan dalam pelaksanaan GLS dan (4) upaya yang dilakukan guna mengatasi hambatan dalam pelaksanaan GLS. Metode yang digunakan ialah metode survey dengan pendekatan kuantitatif dengan menyebarkan kuesioner dan wawancara untuk pengumpulan data. Perolehan hasil penelitian menunjukkan : (1) pelaksanaan GLS di SDN 006 Buahbatu, SDN 184 Buahbatu, SDN 246 Margacinta dan SDN 095 Kebonjati sudah dilaksanakan sesuai dengan pembiasaan 15 menit membaca sebelum KBM dimulai, adanya sudut baca ditiap kelas dengan dilengkapi beragam buku bacaan, (2) terdapat pengaruh antara GLS terhadap Minat Baca peserta didik kelas IV sebesar 29,7%, (3) terdapat beberapa hambatan dalam pelaksanaan GLS diantaranya peserta didik merasa cepat bosan saat membaca, kurangnya dana untuk mendukung fasilitas pelaksanaan GLS, kurang beragamnya variasi buku yang disediakan, dan yang terakhir kurangnya minat peserta didik untuk mengunjungi perpustakaan, (4) upaya yang dapat dilakukan untuk mengatasi hambatan yang ada diantaranya dengan melakukan ice breaking agar peserta didik tidak merasa bosan,membuat proposal mengenai dana kepada pemerintah untuk mendukung fasilitas dalam pelaksaan GLS dengan menyiapkan beragam jenis bahan bacaan, dan menata perpustakaan dengan semenarik mungkin agar dapat menarik minat peserta didik. Kata Kunci : Gerakan Literasi Sekolah, Minat Baca, Sekolah Dasar